2019
DOI: 10.3390/medicina55090516
|View full text |Cite
|
Sign up to set email alerts
|

An Optoelectronic System for Measuring the Range of Motion in Healthy Volunteers: A Cross-Sectional Study

Abstract: Background and Objectives: Within the clinical evaluation of multiple pathologies of the lower limb, the measurement of range of motion (ROM) of its joints is fundamental. To this end, there are various tools, from the goniometer as a reference to more recent devices such as inclinometry-based applications, photo capture applications, or motion capture systems. This study aimed to assess the validity, intra-rater, and inter-rater reliability of the VeloFlex system (VS), which is a new camera-based tool designe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…OMCs represent a powerful tool in the orthopedic clinical practice, mainly when referring to complex joint movement analysis, such as the shoulder joint [35]. These systems allow investigating the joint kinematics in a precise and accurate manner, obtaining quantitative data on joints kinematics [36]. The careful evaluation of postsurgical joint kinematics could allow assessing surgery outcomes to tailor care according to the patient's characteristics, optimizing postsurgical recovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OMCs represent a powerful tool in the orthopedic clinical practice, mainly when referring to complex joint movement analysis, such as the shoulder joint [35]. These systems allow investigating the joint kinematics in a precise and accurate manner, obtaining quantitative data on joints kinematics [36]. The careful evaluation of postsurgical joint kinematics could allow assessing surgery outcomes to tailor care according to the patient's characteristics, optimizing postsurgical recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Even though these systems have not always proved to be suitable in a clinical setting due to their expensiveness and postprocessing analysis, it has been recently shown that they can be more easily used as a reliable measurement tool for shoulder kinematics [36]. The high costs and complexities of experimental setups are outweighed by the impact of these systems in guiding clinical practice and patient follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Veloflex (Deportec, Murcia, Spain) is an optoelectronic system designed to measure ROM and feedback from it. As previously described in Medina-Mirapeix et al (2019) , VF includes three elements: an infrared camera on a tripod, a laptop, and markers to place on the skin. The camera is placed on the adjustable tripod at a distance of 1–1.5 m from the participant and is located at the height of the joint to be examined.…”
Section: Methodsmentioning
confidence: 99%
“…Depending on the proximity of the camera to the joint, the accuracy of the system has been reported between 0.1° and 1° ( Peña García-Orea et al, 2018 ). It has been previously validated to assess ROM in joints of the upper and lower limb, showing excellent intra- and inter-examiner reliability ( Medina-Mirapeix et al, 2019 ; Martín-San Agustín et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…The sample size was based on recommendations in the literature citing ≥21 participants as the minimum for reliability studies 20) . We also considered a previous study of a camerabased tool designed to track joint trajectories and measure movement angles which calculated the minimum sample size for reliability studies to be 25 participants 21) . We included 13 more participants in our final sample in order to increase the study's power.…”
Section: Participants and Methodsmentioning
confidence: 99%